SPECTRAL AND STRATIGRAPHIC COMPOSITION OF THE OIKONYMY OF KARAKALPAKSTAN AND ITS TERRITORIAL DIFFERENCES (Scientific journal of the Fergana State University, 2025)
This article presents information provided by foreign and domestic scientists on the toponymic spectrum and toponymic stratigraphic layer, mainly the spectral-stratigraphic composition of the oikonymy of the Republic of Karakalpakstan, which has a long history in terms of the formation of oikonyms and language features, that is, the distribution of language segments and language layers formed in different periods, their territorial differences were studied and a map was developed. It has been established that Karakalpak, Uzbek, Kazakh, and Turkmen languages are the main ones in the formation of the oikonymy of the Republic of Karakalpakstan.